Explorando o uso de algoritmo genético em jogos digitais - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Digital games moves billions of dollars every year. The largest amount of this money is spent on content. The content keeps the player engaged and the game addictive. This paper introduces the use of genetic algorithm alongside with procedural content generation as an alternative to manual content creation. That way, helping independent developers and small teams on creating digital games. The scientific method utilized in this paper is a comparative method, that investigates individuals, classes, phenomenon or facts, in order to highlight the similarities and differences between them. So, in this paper a genetic algorithm framework was developed and later used on two experiments. The experiment number 1 is a comparison between the classic game Space Invaders and a generic space invaders like game, named InvaderZ, that uses genetic algorithm. The experiment number 2 is a reproduction system that is part of a game. This experiment allowed for a comparison between individuals of different generations of a population as well a comparison between different populations of characters on the game world. During the execution of the experiment 1, validated with the user, the genetic algorithm was capable of enhancing the game mechanics proposed by the game Space Invaders. On the experiment 2, the genetic algorithm was capable of introducing biodiversity in a game where many characters were needed to populate the world. It was then concluded that the genetic algorithm can contribute to the development of digital games, helping the developer on the creation of procedural content, that can make the game a lot more interesting.
Keywords: Engenharia de software; Desenvolvimento de software; Algoritmos genéticos; Jogos digitais; Framework; Software engineering; Software development; Genetic algorithms; Digital games; Framework; CNPQ::CIENCIAS EXATAS E DA TERRA